Probabilitas Osilasi Neutrino dan Kebergantungan Fase CP: Nurhadi, Agus Purwanto - Nurhadi, Nurhadi; Agus Purwanto, Agus Purwanto (Jurnal Fisika dan Aplikasinya, 2025)
Neutrino is an elementary particle of lepton family. When postulated by Pauli in 1930, neutrinos were assumed massless. The standard model of particle physics predicts that neutrinos are also massless. But, in 1998, Super-Kamiokande experiment successfully observe neutrino oscillations in nature. The phenomenon of neutrino oscillations can be explained only if neutrinos have mass. Currently there are three known neutrino flavor i.e electron neutrinos, mu neutrinos, and tau neutrinos. Eigen state of flavor and eigen state of neutrino masses connected by a unitary matrix MNS (Maki-Nakagawa-Sakata), who has four parameters, namely three angles and the one phase CP. In this paper examined three generations of neutrino oscillation probability in both the vacuum and the matter and the dependence of the phase CP.